Synthesis and Characterization of a-Aminophosphonic Acids Containing Adenine - Kong, Du-Lin; Wu, Ming-Shu; Han, Chang-Ri; Ma, Jing-Ya; Wan, De-Hui (Asian Journal of Chemistry, 2011)
Seven novel a-aminophosphonic acids containing adenine 2 were synthesized by the three component condensation reactions of adenine with triphenyl phosphite and aldehydes 1 in presence of acetic acid and xylene. The product structures were characterized by IR and NMR spectral data and elemental analyses.